Genetic and phenotypic spectrum associated with IFIH1 gain‐of‐function. Issue 4 (14th January 2020) - Rice, Gillian I.; Park, Sehoon; Gavazzi, Francesco; Adang, Laura A.; Ayuk, Loveline A.; Van Eyck, Lien; Seabra, Luis; Barrea, Christophe; Battini, Roberta; Belot, Alexandre; Berg, Stefan; Billette de Villemeur, Thierry; et al.
Abstract: IFIH1 gain‐of‐function has been reported as a cause of a type I interferonopathy encompassing a spectrum of autoinflammatory phenotypes including Aicardi–Goutières syndrome and Singleton Merten syndrome. Ascertaining patients through a European and North American collaboration, we set out to describe the molecular, clinical and interferon status of a cohort of individuals with pathogenic heterozygous mutations in IFIH1 . We identified 74 individuals from 51 families segregating a total of 27 likely pathogenic mutations in IFIH1 . Ten adult individuals, 13.5% of all mutation carriers, were clinically asymptomatic (with seven of these aged over 50 years). All mutations were associated with enhanced type I interferon signaling, including six variants (22%) which were predicted as benign according to multiple in silico pathogenicity programs. The identified mutations cluster close to the ATP binding region of the protein. These data confirm variable expression and nonpenetrance as important characteristics of the IFIH1 genotype, a consistent association with enhanced type I interferon signaling, and a common mutational mechanism involving increased RNA binding affinity or decreased efficiency of ATP hydrolysis and filament disassembly rate.